Effect of a low‐fat diet on serum triglyceride and cholesterol concentrations and lipoprotein profiles in Miniature Schnauzers with hypertriglyceridemia - Xenoulis, Panagiotis G. (J Vet Intern Med, 2020)
BACKGROUND: Hypertriglyceridemia is common in Miniature Schnauzer (MS). Dietary management of hypertriglyceridemia is important, but no studies are available. HYPOTHESIS/OBJECTIVES: To evaluate the effect of a commercially available low‐fat diet on serum triglyceride and cholesterol concentrations and lipoprotein profiles in MS with hypertriglyceridemia. ANIMALS: Sixteen MS with hypertriglyceridemia and 28 MS without hypertriglyceridemia. METHODS: Prospective clinical trial. Four blood samples (1‐2 months before and 1 day before diet change and 2 and 3 months after the dogs were fed the low‐fat diet) were collected from the MS with hypertriglyceridemia. RESULTS: Serum triglyceride concentrations for the 2 samples after the diet change (median of sample 3 = 177 mg/dL; range, 48‐498; median of sample 4 = 168 mg/dL; range, 77‐745) were significantly lower than the 2 samples before the diet change (median of sample 1 = 480 mg/dL; range, 181‐1320; median of sample 2 = 493 mg/dL; range, 114‐1395; P < .001). Serum cholesterol concentrations for the 2 samples after the diet change (mean for sample 3 = 257 mg/dL, SD = 82.2; mean for sample 4 = 178 mg/dL, SD = 87.4) were also significantly lower than the 2 samples before the diet change (mean for sample 1 = 381 mg/dL, SD = 146.1; mean for sample 2 = 380 mg/dL, SD = 134.7; P < .001). Before the diet change, 15/16 (94%) of hyperlipidemic MS were classified as hyperlipidemic based on their lipoprotein profiles alone. After the diet change, significantly fewer MS (7/16; 44%; odds ratio = 19.3; 95% CI = 2.0‐184.0; P = .006) were classified as hyperlipidemic based on lipoprotein profile analysis. CONCLUSIONS AND CLINICAL IMPORTANCE: The study diet was effective in reducing serum triglyceride and cholesterol concentrations and correcting lipoprotein profiles in MS with hypertriglyceridemia.